Circular economy strategies in the hotel industry: A bibliometric analysis - Garces, Monica Paola Lopez; Ivan, Ronquillo Panchana Roger; Zurita, Maria Jose Ortiz (International Journal of Innovative Research and Scientific Studies, 2025)
This study addresses the primary trends in research, scientific productivity, and global collaboration networks while conducting a bibliometric examination of circular economy tactics in the hotel business. Publications from databases like Scopus and Web of Science are analyzed to identify key players and the most important journals in the subject. The findings indicate a rise in scholarly work on the circular economy in the hospitality industry, emphasizing issues like resource efficiency and waste management. Despite this expansion, there are still obstacles to implementing circular practices, especially when it comes to incorporating new technologies and calculating the financial impact. It is determined that in order to encourage the implementation of these techniques and accomplish sustainability objectives in the hotel industry, cooperation between academia and industry is crucial.